TRANSLATION PROCEDURES OF PHYSICS TERMS IN THE PHYSICS BILINGUAL BOOK FOR SENIOR HIGH SCHOOL YEAR XI - Sari, Mareta Permata; Yuliasri, Issy (ELT Forum: Journal of English Language Teaching, 2017)
This study attempted to analyze the use of translation procedures and their accuracy. The objectives of the study were to describe the translation procedures used to translate the Physics terms and to identify their accuracy in Physics Bilingual Book for Senior High School Year XI. This research was conducted qualitatively. This study applied the theory proposed by Vinay and Darbelnet (in Hatim and Munday 2004:30) about translation procedures and the accuracy criteria of translation assessment by Nababan (2012:50). The results of the study showed that there were 119 data of Physics terms and three translation procedures found in this study. The three translation procedures were equivalence, calque and transposition. The translation procedure mostly used was equivalence, followed by calque and transposition. In terms of accuracy, three raters found that around 99.15% of the data were translated accurately, whereas the rest 0.84% of the data were inaccurately translated. The translation procedure with the highest accuracy was equivalence, followed by calque and transposition. Thus, the equivalence procedure was mostly used and had the highest accuracy rating in this research, followed by calque and transposition.